CONTOH TINGKAH LAKU AFEKTIF CONTOH TINGKAH LAKU AFEKTIF: CONTOH TINGKAH LAKU AFEKTIF - Iwan B. Jassin; Frezy Paputungan; Zihan Usman (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
The article discusses examples of affective behavior that are commonly observed in everyday life. These examples will include verbal and nonverbal expressions that reflect the different types of emotions we experience frequently. By understanding these examples, readers will be able to recognize and understand affective behavior in themselves and others, as well as interpret and respond to it better. This article is presented using qualitative methods. Affective behavior is Affective behavior is behavior that involves different emotions such as fear, anger, sadness, joy, disappointment, excitement, anger, fear, and others. And also the affective domain is a behavior that includes feelings, emotions, interests, attitudes, ways of adjustment, and appreciation. Understanding affective behavior is important in interacting with others and understanding yourself. Research on affective behavior can provide useful insights in the fields of psychology, social sciences, and communications, and can contribute to the development of smarter technologies for automated emotion recognition or emotion-based facial recognition. With a deeper understanding of affective behavior, it is hoped that we can improve the quality of social interaction, strengthen interpersonal relationships, and increase self-understanding and that of others in everyday life.